ESTRO consensus guideline on target volume delineation for elective radiation therapy of early stage breast cancer. Issue 1 (January 2015) - Offersen, Birgitte V.; Boersma, Liesbeth J.; Kirkove, Carine; Hol, Sandra; Aznar, Marianne C.; Biete Sola, Albert; Kirova, Youlia M.; Pignol, Jean-Philippe; Remouchamps, Vincent; Verhoeven, Karolien; Weltens, Caroline; Arenas, Meritxell; et al.
Abstract: Background and purpose: Delineation of clinical target volumes (CTVs) is a weak link in radiation therapy (RT), and large inter-observer variation is seen in breast cancer patients. Several guidelines have been proposed, but most result in larger CTVs than based on conventional simulator-based RT. The aim was to develop a delineation guideline obtained by consensus between a broad European group of radiation oncologists. Material and methods: During ESTRO teaching courses on breast cancer, teachers sought consensus on delineation of CTV through dialogue based on cases. One teacher delineated CTV on CT scans of 2 patients, followed by discussion and adaptation of the delineation. The consensus established between teachers was sent to other teams working in the same field, both locally and on a national level, for their input. This was followed by developing a broad consensus based on discussions. Results: Borders of the CTV encompassing a 5 mm margin around the large veins, running through the regional lymph node levels were agreed, and for the breast/thoracic wall other vessels were pointed out to guide delineation, with comments on margins for patients with advanced breast cancer. Conclusion: The ESTRO consensus on CTV for elective RT of breast cancer, endorsed by a broad base of the radiation oncology community, is presented to improve consistency.